PENGARUH SUPERVISI DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP MOTIVASI UNTUK PENINGKATAN KINERJA GURU PADA SMA NEGERI 32 JAKARTA - Hendri; Siti (Jurnal Satya Mandiri Manajemen dan Bisnis, 2016)
This study aims to determine the effect of supervision, school leadership, and motivation to the improved performance of teachers at SMAN 32 Jakarta. This research was conducted through questionnaires by teachers at SMAN 32 Jakarta, samples were taken and processed as many as 54 respondents. For data analysis methods using path analysis. Results of this study indicate that simultaneous supervision, school leadership, and motivation direct and significant impact on the improvement of the performance of teachers at SMAN 32 Jakarta, and the results obtained partial processing and data analysis using SPSS 22 shows that Supervision direct and significant impact on motivation teachers work in SMA 32 Jakarta amounting to 0.267 or 26.7%, supervision is not a positiv e direct effect on Teacher Performance in SMA Negeri 32 Jakarta, with the result of calculation of 0,225, or 22.5%, Leadership Principal direct and significant impact on work motivation teachers in SMA Negeri 32 Jakarta, with the result of calculation of 0 ,427, or 42.7%, Leadership Principals do not have direct impact positively on Teacher Performance in SMA Negeri 32 Jakarta, with the result of calculation of 0,244 or 24.4% and working motivation has no direct effect positive on teacher performance SMA Negeri 32 Jakarta, with the result of calculation of 0.106 or 10.6%.